MRI in LARS1 deficiency—Spectrum, patterns, and correlation with acute neurological deterioration - Hammann, Nicole; Lenz, Dominic; Bianzano, Alyssa; Husain, Ralf A.; Forman, Eva; Bernstein, Jonathan A.; Dattner, Tal; Engelen, Marc; Hanson-Kahn, Andrea K.; Isidor, Bertrand; Kotzaeridou, Urania; Tietze, Anna; et al. (Journal of Inherited Metabolic Disease, 2024)
Leucine aminoacyl tRNA-synthetase 1 (LARS1)-deficiency (infantile liver failure syndrome type 1 (ILFS1)) has a multisystemic phenotype including fever-associated acute liver failure (ALF), chronic neurologic abnormalities, and encephalopathic episodes. In order to better characterize encephalopathic episodes and MRI changes, 35 cranial MRIs from 13 individuals with LARS1 deficiency were systematically assessed and neurological phenotype was analyzed. All individuals had developmental delay and 10/13 had seizures. Encephalopathic episodes in 8/13 were typically associated with infections, presented with seizures and reduced consciousness, mostly accompanied by hepatic dysfunction, and recovery in 17/19 episodes. Encephalopathy without hepatic dysfunction occurred in one individual after liver transplantation. On MRI, 5/7 individuals with MRI during acute encephalopathy had deep gray matter and brainstem changes. Supratentorial cortex involvement (6/13) and cerebellar watershed injury (4/13) occurred with seizures and/or encephalopathy. Abnormal brainstem contour on sagittal images (8/13), atrophy (8/13), and myelination delay (8/13) were not clearly associated with encephalopathy. The pattern of deep gray matter and brainstem changes are apparently characteristic of encephalopathy in LARS1-deficiency, differing from patterns of hepatic encephalopathy or metabolic stroke in organic acidurias and mitochondrial diseases. While the pathomechanism remains unclear, fever and energy deficit during infections might be causative; thus, sufficient glucose and protein intake along with pro-active fever management is suggested. As severe episodes were observed during influenza infections, we strongly recommend seasonal vaccination.
CRIS-Team Scopus Importer:2024-07-19
Keywords: acute liver failure; aminoacyl-tRNA synthetase deficiencies; cerebellar watershed; encephalopathy; ILFS1; LARS1; metabolic stroke; MRI; thalamus